RAW MATERIALS ANALYSIS OF TEXTILE INDUSTRY USING THE PRINCIPAL COMPONENT ANALYSIS METHOD IN DETERMINING INVESTMENT WITH REAL OPTIONS - Dwiutari Tjiptoyuwon, Gabriella
The textile industry has become the first contribution of the non-oil sector. Unfortunately, the supply of raw materials, can’t fulfill domestic textile industry’s demand. It forced the nation to import the raw materials. One of them is Paraxylene, a raw material that is often used to manufacture Terephalate and PTA which are materials for making plastics and textiles. Based on the problems that exist until now, research needs to be done to address textile raw materials in Indonesia. This research was conducted in three stages, namely analyzing the dominant raw materials, predicting the main raw materials, and investing in building a factory. The data used is data for 2016-2018 from APSyFI (Association of Indonesian Fiber and Filament Yarn Manufacturers). The method used to analyze dominant raw materials is Principal Component Analysis (PCA). Principal Component Analysis will be carried out by utilizing the covariance matrix and corelation matrix, to look for dominant raw materials and compare the results for both matrix. Furthermore, the volume of dominant material obtained, namely Paraxylena, will be predicted for 2019 using the Time Series Analysis method. From the predictions obtained that the need for Paraxylena increases in 2019, so the authors propose to invest in building Paraxylena factory with a production capacity of 400,000 tons / year to meet domestic needs. Plant construction will require a feasibility analysis, which is carried out using the DCF method. However, the DCF method does not have a flexibility of the market, so the project value isn’t optimal. Therefore, Real Options Analysis will be carried out, which is a valuation method that is appropriate to the value of the project, so that it can be built with a profitable investment strategy. With Monte Carlo Simulation, project cash flow will be built and the project volatility as market uncertainty. The Binomial Lattice method is one of the methods used to calculate real options, so in the end it will be obtained the value of project with or without option